THU0039 Regulation of ASK-1 Expression by Microrna-17 and Its Correlation with Rheumatoid Arthritis Pathogenesis. (9th June 2015) - Akhtar, N.; Ahmed, S.
Abstract : Background: Deregulated expression of microRNAs (miRs) has shown to be critical for the pathogenesis of rheumatoid arthritis (RA) 1, 2 . Apoptosis signal regulating kinase (ASK)-1, a member of MAP3K family upstream of p38 MAPK has recently been associated with RA pathogenesis 3 . Objectives: To evaluate the role of ASK-1 in RA pathogenesis and its epigenetic regulation by miRNA in human RA synovial fibroblasts (RA-FLS) and rat adjuvant-induced arthritis (AIA) model. Methods: Bioinformatics analysis was performed to identify the predicted miRNA targets at 3'UTR region of ASK-1 gene. ASK-1 expression in FLS from RA, osteoarthritis (OA), or non-diseased (NH) donors was compared and correlated with miR-17 expression using qRT-PCR and Western immunoblotting. Effect of IL-1β (10 ng/ml) or TNF-α (20 ng/ml) stimulation alone or in the presence of ASK-1 inhibitor (TC-ASK-10) on ASK-1 mRNA and protein and IL-6 production was examined using ELISA. Transfection of RA-FLS with a 3'UTR reporter construct and pre-miRNAs was performed to verify the miRNA: mRNA interaction. Effect of overexpression and inhibition of miR-17 on ASK-1 expression was evaluated by transient transfections of RA-FLS. Findings from human FLS were validated in vivo using a rat AIA model. Results: Bioinformatics analysis predicted miR-17 binding sites at 3'UTR region of ASK-1. MiR-17 expression was down-regulated by ∼70% in RA-FLS as compared to NH-FLS (p<0.05; n=5) and inversely correlated with a significant increase in the expression of ASK-1 mRNA (∼2.3-fold) and protein (p<0.05). However, no significant correlation was observed between miR-17 or ASK-1 expression in OA-FLS compared to NH-FLS or tissue. Stimulation of RA-FLS with IL-1β or TNF-α for 24h further suppressed the expression of miR-17, with a concomitant increase in ASK-1 mRNA (∼2.2 to 12.5 fold) and protein expression (p<0.05). Interestingly, inhibition of ASK-1 using TC-ASK-10 (12.5 μM) resulted in a marked attenuation of p-p38 MAPK and IL-6 expression in RA-FLS. Co-transfection of RA-FLS with the ASK-1 luciferase reporter construct and pre-miR-17 significantly suppressed the luciferase activity by ∼29% (p<0.05). Overexpression of miR-17 inhibited the expression of ASK-1 (∼25%), whereas transfection with miR-17 inhibitors enhanced its expression (∼22%) in RA-FLS (p<0.05). In rat AIA model, ASK-1 expression increased in with the disease progression, and correlated with the reduced miR-17 expression and enhanced p-p38 MAPK and IL-6 expression. These data suggest that ASK-1 mRNA is a direct target of miRNA-17. Conclusions: This study provides evidence for the role of ASK-1 in RA pathogenesis and a novel mechanism of its epigenetic regulation by miR-17 in RA-FLS and rat AIA model. References: Wittman J, et al. Ann. Rheum. Dis. 2011; 70 (Suppl 1): i92-i96. Duroux-Richerd I, et al. Arthritis Rheum. 2012; 64(1):11-20. Mnich SJ, et al. Int. Immunol. 2010;10:1170-76. Acknowledgements: This study was supported by the NIH grant AR063104 (S.A.), The Arthritis Foundation Innovative Research Grant (S.A.), and the Start-up funds from Washington State University. Disclosure of Interest: None declared